2015
DOI: 10.1186/s12284-015-0052-7
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome profiling of the spl5 mutant reveals that SPL5 has a negative role in the biosynthesis of serotonin for rice disease resistance

Abstract: BackgroundRice mutant, spl5 (spotted leaf 5), has spontaneous hypersensitive-like lesions on its leaves and shows enhanced resistance to pathogens, indicating that SPL5 plays a role in programmed cell death (PCD) and disease resistance. To understand the molecular mechanism of SPL5 gene, we investigated the transcriptome profiles of the spl5 mutant leaves with few lesions (FL) and leaves with many lesions (ML) compared to the wild-type (WT) leaves respectively by microarray.ResultsThe data from microarray reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 48 publications
0
20
0
1
Order By: Relevance
“…Indeed, we found that expression of the genes aroA and aroC , required for biosynthesis of chorismate from shikimate [ 72 , 73 ], obviously increased in the lrd6-6 mutant ( Fig 9A ). Because chorismate is required for biosynthesis of both serotonin and lignin [ 74 , 75 ], the increased expression of aroA and aroC would lead to accumulation of the antimicrobial metabolites, serotonin and lignin. We then found that expression of the downstream genes essential for respective biosynthesis of serotonin and lignin initiated from chorismate (for biosynthesis of serotonin: As , Igps , Ts and Tdc ; for biosynthesis of lignin: Pal , Ptal , 4Cl , Ccr , F5h , Cad and Pox ) increased in the lrd6-6 mutant ( Fig 9A ), supporting our notion that the antimicrobial metabolites, serotonin and lignin, would accumulate in the lrd6-6 mutant.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, we found that expression of the genes aroA and aroC , required for biosynthesis of chorismate from shikimate [ 72 , 73 ], obviously increased in the lrd6-6 mutant ( Fig 9A ). Because chorismate is required for biosynthesis of both serotonin and lignin [ 74 , 75 ], the increased expression of aroA and aroC would lead to accumulation of the antimicrobial metabolites, serotonin and lignin. We then found that expression of the downstream genes essential for respective biosynthesis of serotonin and lignin initiated from chorismate (for biosynthesis of serotonin: As , Igps , Ts and Tdc ; for biosynthesis of lignin: Pal , Ptal , 4Cl , Ccr , F5h , Cad and Pox ) increased in the lrd6-6 mutant ( Fig 9A ), supporting our notion that the antimicrobial metabolites, serotonin and lignin, would accumulate in the lrd6-6 mutant.…”
Section: Resultsmentioning
confidence: 99%
“…This result suggested that biosynthesis of these phytoalexins might be highly activated in the lrd6-6 mutant. Previous reports have shown that the WRKY transcription factor OsWRKY14 is required for serotonin biosynthesis through regulating the expression of genes TS ( tryptophan synthase ) and TDC ( tryptophan decarboxylase ) [ 74 , 77 ] and that the MPK genes OsMPK3 , OsMPK6 and OsMPK4 regulate the biosynthesis of lignin and phytoalexins [ 75 , 78 ]. When determining the expression of these genes, with the exception of OsMPK6 , we found that the expression of all these genes was highly increased in the lrd6-6 mutant compared with Kitaake (Figs 9B and 10B ), further supporting our notion that antimicrobial metabolites accumulated in the lrd6-6 mutant.…”
Section: Resultsmentioning
confidence: 99%
“…Serotonin content was detected as published method (Jin et al ., ). 200 mg leaf tissue at the heading stage was ground with liquid nitrogen into a powder and soaked in 1 mL 100% methanol.…”
Section: Methodsmentioning
confidence: 97%
“…Potential pathways for OsACL-A2-mediated innate immunity in rice Catalysed by OsSL (Fujiwara et al, 2010), serotonin has been reported to play a critical role in disease resistance (Hayashi et al, 2016;Jin et al, 2015). It served as a substrate for peroxidase in the presence of hydrogen peroxide to form a complex mixture of oligomerics that function as a physical barrier against the spread of pathogen infections in infected rice leaves (Ishihara et al, 2011).…”
Section: The Ups-mediated Degradation Of Spl30 N343ymentioning
confidence: 99%
“…活性氧(reactive oxygen species, ROS)在水稻类病变发生的过程中也起 着很重要的作用 [21] , H 2 O 2 以及O 2 可能导致氧迸发, 进 而导致水稻细胞程序性死亡, 产生类病变. SPL5编码 剪接因子3b的亚基3(SF3b3), 它可能通过RNAs前体剪 接作用控制细胞死亡及防御反应 [22] . 此外, OsLSD1基 因的表达是光诱导或暗抑制, 同时OsLSD1在调节植物 PCD方面起负调控的作用, 所以在光照下会促进 OsLSD1产生病斑 [23] .…”
Section: 水稻是世界上重要的粮食作物之一 同时也是重unclassified